Thursday

April 17, 2014

April 17, 2014

Posted by **sandy** on Sunday, November 25, 2012 at 6:33pm.

Thanks

- algebra -
**Reiny**, Sunday, November 25, 2012 at 9:09pm13 lnx = (lnx)^2

let lnx = y

13y = y^2

y^2 - 13y = 0

y(y-13) = 0

y = 0 or y = 13

then lnx = 0 , but that is undefined

or

lnx = 13

x = e^13

**Related Questions**

Math differentiation - 1. y = x^x 2. y = (sin^2xtan^4x)/(x^2+1)^2 3. y = x^(1/x...

Math - ln x^2(x+1)/x+2 Write in terms of ln(x), ln(x+1), and ln(x+2) is the ...

Help, Math. - Solve: 3e2x + 2 = 50 a. ln 8 b. ln 0.25 c. ln 14 d. 0.5ln 16...

ALGEBRA - Contract the expressions. That is, use the properties of logarithms to...

algebra - can someone plzs help me solve the equations by finding the exact ...

math - Express y as a function of x. C is a positive number. 3 ln y= 1/2ln (2x+1...

Algebra - how would you solve these two equations. ln x + ln(x+1)=1 ln(x+5) = ln...

Math - Given the axioms: ln x = definite integral from 1 to x of 1/t dt ln e = 1...

Math - What does the following infinite series starting at k=2 converge to: &...

solving for x math - 2e^(4x^2)=3 how do i solve for x. do i use the ln methode ...